Persepsi Masyarakat terhadap Tajdid al-Nikah (Pembaharuan Nikah): Studi Kasus di Dusun Dawuhan Suco Lor Maesan Bondowoso - Imam Syarbini (Al-Adillah: Jurnal Hukum Islam, 2022)
Tajdid Nikah is renewing the marriage, with the meaning that there has been a valid marriage contract according to the syara', then with the intention of being Ihtiyath (be careful) and making the heart comfortable, the marriage contract is carried out one more time or more. If we classify the occurrence of tajdid Nikah in the hamlet of Dawuhan Suco Lor, there are two kinds, first the newlyweds, this part is divided into two more, namely; (1) based on auspicious days (according to Javanese calculations), for example when registering, KUA determines the date of August 15, 2022, while according to Javanese calculations it is a good day on August 2, 2022, then the newlyweds have a contract first with the Kiai, then on August 15, 2022, the contract will be again at KUA for the second time. (2) the newlywed couple or one of them, whose age does not meet the marriage law, then the marriage is still carried out, after the age meets the marriage law, the contract is again held at the KUA. Second, old brides, these two also have two, (1) because there, for one year, must occur, experiencing difficulties, difficulties in overcoming difficulties, words are thrown out without realizing it. (2) based on a figure's suggestion, for example, if the contract is repeated, the sustenance will be increased, the household life will be more harmonious and so on. With regard to the 'ulama' Tajdid Nikah, there are several differences of opinion. The first is of the opinion that the Tajdid Nikah is not acceptable because it can damage the first marriage contract. The second opinion of the majority of scholars, who say that the Tajdid Nikah is legal and does not damage the marriage contract, not as an acknowledgment of the damage to the first contract. So that it does not reduce the number of talak counts, because most of the purposes of tajdid are as a form of confirmation or caution.